Analisis Perbandingan Resiko dan Kinerja Biaya Pada Proyek Konstruksi antara Pemerintah dan Swasta - nanda, satria tri (Komunitas Manajemen Kompetitif, 2016)
Abstract: of construction contract risk in construction contract risks toward cost performance in either state-owned or private-owned projects. The population included the key person-level employees of Operation Division I PT. PP (Persero) Tbk. The sample consisted of 100 informants who were selected by using cluster sampling method. The variables are construction contract risks, consists of: work scope, project execution time, lumpsum price, payment method, additional/reduction work, and contract ending as independent variable, while cost performance used as dependent variable. The data were analyzed with compare means analysis using SPSS 17 for windows. The results show that the project cost control in state-owned project is already effective, while in private-owned project is still not effective. In the perspective of construction contract risk, either in state-owned or private-owned projects, both are facing the same high risk of discrepancies. Keywords: Construction Contract Risk, Risk Management, Effectivity, Project Cost